Optimal frequency/time combination of whole‐body vibration training for improving muscle size and strength of people with age‐related muscle loss (sarcopenia): A randomized controlled trial. Issue 10 (31st August 2016) - Wei, Ning; Pang, Marco YC; Ng, Shamay SM; Ng, Gabriel YF
Abstract: Aim: To determine the optimal combination of frequency and exposure time of a whole‐body vibration (WBV) training program for improving muscle performance of older people with age‐related muscle loss. Methods: A total of 80 community‐dwelling older adults with age‐related muscle loss were randomly divided into four equal groups, namely, low‐frequency long duration (20 Hz × 720 s), medium‐frequency medium duration (40 Hz × 360 s), high‐frequency short duration (60 Hz × 240 s) and control (no training) for 12‐week WBV training and 12‐week follow up. Assessments were carried out at baseline, mid‐intervention, post‐intervention, mid‐follow up, follow up for the cross‐sectional area of the vastus medialis, isometric knee extension strength at 90°, and isokinetic knee extension at 60°/s and 180°/s. Results: There was a significant time × group interaction effect in isokinetic knee extension at 180°/s. Significant time effects were found in all muscle strength outcome variables. Group differences in percentage change from baseline were significant between medium‐frequency medium duration and control on isokinetic knee extension at 180°/s and 60°/s. No changes were found in the cross‐sectional area of the vastus medialis. Conclusions: With the total number of vibrations controlled, the combination of 40 Hz and 360 s of WBV exercise had the best outcome among all other combinations tested. The improvements in knee extension performance can be maintained for 12 weeks after cessation of WBV training.Geriatr Gerontol Int 2017; 17: 1412–1420.